Those cozy pitches - Soccer memories of a process of social identity construction (PerCursos, 2023)
This article sets out to demonstrate the importance of soccer as a way of organizing identities in a poor neighbourhood on the outskirts of Porto Alegre - RS, Restinga. The research found that the practices surrounding this sport were a significant contribution to the fight against social and racial segregation in this neighborhood. We saw the importance of memory as a factor in articulating identities and evoking practices of anti-racist social struggles that took place in other times and territories, but which have a strong cultural influence on the daily lives of the population of workers/residents of Restinga. The field research was carried out through interviews with various individuals who were part of the process of appropriating the territory of this neighborhood through soccer. Ethnographic walks and game observation were also carried out. The first part briefly describes the characteristics of Restinga and the process of segregation that gave rise to this territory, followed by a description of the historical struggle of the city's black population for the right to organize soccer teams and how this process relates to Restinga. Finally, the complex relationships between the protagonists and the developments and gaps that we were able to observe from the research are pointed out. The right to the city, broadly understood, must also incorporate the possibility for workers and residents of the periphery to produce culture and be protagonists in the construction of their identities. In Restinga, soccer was one of the vehicles for this affirmation.
Keywords: soccer; segregation; memory; identity; racial issue